2021
DOI: 10.3390/rs13112202
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Landsat NDVI Sequences to Explain Wheat Yield Variation in Fields in Western Australia

Abstract: Long-term maps of within-field crop yield can help farmers understand how yield varies in time and space and optimise crop management. This study investigates the use of Landsat NDVI sequences for estimating wheat yields in fields in Western Australia (WA). By fitting statistical crop growth curves, identifying the timing and intensity of phenological events, the best single integrated NDVI metric in any year was used to estimate yield. The hypotheses were that: (1) yield estimation could be improved by incorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The vegetative index has been identified as an efficient and reliable tool for high‐throughput phenotyping of wheat populations against various biological traits like photosynthesis, green leaf biomass, chlorophyll contents including stress tolerance (Cabrera‐Bosquet et al, 2011; Gitelson et al, 2003; Kizilgeci et al, 2021; Li et al, 2020). Recently, the potential of NDVI metrics has been shown to estimate yield variation in field grown wheat in Western Australia (Shen & Evans, 2021). In addition, NDVI has also been found an effective indicator of vegetation response under terminal drought stress (Bhandari et al, 2021; Condorelli et al, 2018; Naser et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The vegetative index has been identified as an efficient and reliable tool for high‐throughput phenotyping of wheat populations against various biological traits like photosynthesis, green leaf biomass, chlorophyll contents including stress tolerance (Cabrera‐Bosquet et al, 2011; Gitelson et al, 2003; Kizilgeci et al, 2021; Li et al, 2020). Recently, the potential of NDVI metrics has been shown to estimate yield variation in field grown wheat in Western Australia (Shen & Evans, 2021). In addition, NDVI has also been found an effective indicator of vegetation response under terminal drought stress (Bhandari et al, 2021; Condorelli et al, 2018; Naser et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Climatic factors, evapotranspiration, water quality, and topography all have an impact on crop growth (Jia et al, 2020). NDVI can be used to examine crop growth and its relationship with various factors to reveal the important factors for intervention and tracking climate adaptation (Phan et al, 2021;Shen and Evans, 2021;Yadav and Geli, 2021;Rigden et al, 2022). For instance, in China, precipitation was found to be the leading cause of agricultural failure over other factors (Peng et al, 2008), whereas Lamchin et al (2018) found temperature to be the most influential factor in vegetation growth in the Asia region.…”
Section: Remote Sensing Technology For Climate Change Adaptation Trac...mentioning
confidence: 99%
“…The impact of climate change on farming systems in Sub-Saharan Africa has also been tracked using an 8 km resolution AVHRR-NDVI (Vrieling et al, 2011). A sequence of Landsat 30-meter resolution NDVI has been used by Shen and Evans (2021) for estimating wheat yields in fields.…”
Section: Options and Challenges For Developing A Biomass Climate Adap...mentioning
confidence: 99%
See 1 more Smart Citation
“…It combines spatial smoothing by use of spatial weights with temporal smoothing by growth curve estimation to improve estimation of land surface phenology from Landsat NDVI. Because it is not dependent on individual cells having sufficient cloud-free images within the growing season, SWGC enables phenology detection at more cells than non-spatial approaches which typically exclude cells with insufficient observations (e.g., [44,49]).…”
Section: Introductionmentioning
confidence: 99%